To Pay or Not to Pay Community Preceptors? That Is a Question …. Issue 3 (27th May 2019) - Christner, Jennifer G.; Beck Dallaghan, Gary; Briscoe, Greg; Graziano, Scott; Mylona, Elza; Wood, Sarah; Power, David V.
Abstract: Phenomenon : Pairing medical students with community-based preceptors has provided unique medical education advantages. However, due to an increase in the number of M.D.-granting medical schools and medical school class sizes, academic medical institutions have struggled to recruit community preceptors to teach their students. This task has been made more difficult due to rising pressures upon institutions and clinicians—for example, increased productivity demands, greater volume and oversight of electronic health record documentation, and competition for community preceptors from both D.O. and non-U.S.-based medical schools. Although academic institutions have historically relied largely on altruistic motives and intrinsic rewards to actively engage and retain community-based preceptors, alternative models have arisen, chiefly those in which community-based preceptors are explicitly compensated for teaching. Approach : To study this phenomenon, representatives of the Alliance for Clinical Education developed and deployed a 31-item survey accompanied with a subset of free text questions to the collective membership of its 8-member constituent organizations. Survey questions explored if community preceptors were compensated indirectly or directly and what types of compensation were provided, if any. There were 188 surveys analyzed, with an estimated response rate of 18.2%. Findings : Twenty-six percent of respondents indicated they compensate community preceptors directly and/or indirectly. Respondents discussed their motivations for payment (or nonpayment), mechanisms for paying, aspirations to pay, and expectations of the recipient. No statistically significant association was found when comparing responses of paid versus not paid by region. Free text responses provided additional insight regarding payment considerations, institutional competition, recruitment/retention, recognition, and education issues. Insights : Increasingly, medical schools are finding it necessary to provide funding for community preceptors in order to retain them. New creative forms of compensation to community preceptors may prove important in the future for this vital aspect of medical student education.